Pentachlorophenol mediated regulation of DAMPs and inflammation: In vitro study. (September 2022) - Thota, Shilpa; Begum, Rizwana; Kaur, Gagandeep; Bagam, Prathyusha; Dorsey, Waneene; Batra, Sanjay
Abstract: Pentachlorophenol (PCP) was once a widely employed organochlorine pesticide and wood preservative in United States. Due to its toxicity, the U.S. Environmental Protection Agency has classified it as a restricted-use pesticide and established as a liver carcinogen. Earlier reports have indicated increased production of inflammatory mediators like IL-1β and TNF-α by immune cells, including NK cells, lymphocytes, or monocytes -on PCP exposure. Yet, there is only scant information available regarding the detailed molecular mechanisms affected by acute or chronic exposure of humans to PCP. Considering this, we examined PCP-induced inflammation and downstream signaling events in-(a) human lung adenocarcinoma cells (A549) with type II alveolar epithelial characteristics; and (b) human liver carcinoma cells (HepG2). Treatment of these cells with 1 μM and 10 μM concentration of PCP for 24 h duration resulted in a significant induction of cytokines/chemokines including IL-1β, IL-6, TNF-α, IL-8, CCL2, and CCL5. Assessment of mRNA expression showed upregulated levels of danger-associated molecular patterns (DAMPs)-high mobility group box-1 (HMGB1) and heat shock protein 70 (Hsp70) as well as TLR-4 receptor in PCP-challenged cells. Increased expression of transcription factors-NF-κB and STAT3 provide further insight into the molecular mechanisms underlying PCP-induced toxicity/pathology. Interestingly, antibody-mediated neutralization of DAMPs abrogates PCP-mediated transcriptional induction of cytokines, chemokines and transcription factors in HepG2 and A549 cells. Overall, our findings demonstrate the important role of DAMPs in PCP-induced inflammatory responses. Graphical abstract: Unlabelled Image Highlights: Pentachlorophenol (PCP) increased the extracellular release of DAMPs by lung and liver epithelial cells. Increased expression of pattern recognition and chemokine receptors was observed in PCP-challenged cells. PCP exposure resulted in increased secretion of cytokines and chemokines by A549 and HepG2 cells. Induction/activation of- transcription factors and master cytokinesprovide mechanistic insights into PCP-induced responses. Antibody mediated neutralization of DAMPs abrogated PCP-induced inflammation.